Characterisation of portfolios of distributed energy resources under uncertainty - Aunedi,M; Štrbac,G; Pudjianto,D (2009)
The paper proposes a model to determine the optimal strategy of offering electricity at the day-ahead market for a portfolio of Distributed Energy Resources. The stochastic nature of the problem is taken into account through uncertainty of generator output and forecasts of day-ahead and imbalance prices. The model attempts to maximise the expected profit of the portfolio when exposed to imbalance prices and output uncertainty. Portfolios analysed included conventional generators, wind generators, or both. The results indicate that the proposed approach is able to adapt the offering strategy to the risk profile in different times of the day. Also, significant synergic effects are demonstrated when wind and conventional generators are aggregated into a single portfolio, due to increased flexibility in internal portfolio balancing.